Сила и бессилие: внешняя политика Вашингтона, 1945-1982 гг. - Мельников Юрий Михайлович (Политиздат, 1983)
Экземпляры: КХ (20241108) / Инвентарный номер: 795895 / Сис.шифр: 32И / Авт.знак: М 48 / ГРНТИ: 11 / ББК: 66